Internalisasi Nilai-Nilai Islam Untuk Pembentukan Akhlak Dalam Pembelajaran Bahasa Indonesia Di SD Muhammadiyah 16 Karangasem Laweyan Surakarta - NOPIARTI, Umi, Prof. Dr. Abdul Ngalim, M.Hum, Drs. Budi Sutrisno, M.Pd (2015)
The purpose of the study is described. 1) The planning process of the internalization Islamic values for moral formation in learning Indonesia language. 2) The Organizing process of internalization Islamic values for moral formation in learning Indonesia language.3) The process of internalization Islamic values for moral formation in learning Indonesia language.4) Evaluation of the internalization Islamic values for moral formation in learning Indonesia language .5) The factors supporting and inhibiting in the process of internalization Islamic values for moral formation in learning Indonesia language. This type of research is qualitative and use an ethnographic approach to research. Subjects were principal, teachers, and students. the Methods of data collection use in-depth interviews, observation, and documentation. The Analysis use a triangulation. Results of the research are: 1) The process of internalization Islamic values for moral formation in learning Indonesia language in SD Muhammadiyah Surakarta 16 Karangasem has done with some reference to the teacher's task according to the standard of teacher work.2) The Organizing process internalization of Islamic values for moral formation in Indonesian language learning in SD Muhammadiyah Surakarta 16 Karangasem focused on language acquisition, not on language learning. 3) The process of internalization Islamic values for moral formation in learning Indonesia in SD Muhammadiyah Surakarta Karangasem 16 includes learning implementation strategies, that use of media and learning resources, and the implementation has done with focus of the characteristics SD Muhammadiyah 16 education in Karangasem Surakarta.4 ) Evaluation of the process internalization of Islamic values for moral formation in learning Indonesia language in SD Muhammadiyah Surakarta Karangasem 16 includes classroom-based assessment to obtain information on the development and progress competence and achievement students.5) Supporting factors in the process of internalization of Islamic values for morals in the learning Indonesia language in SD Muhammadiyah Surakarta 16 Karangasem is formed on institutional support, human resources, and the support of parents. The factors that barrier is the limited of time.